2017
DOI: 10.1016/j.jmb.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Synthetic Lethality and Network Biology to Overcome EGFR Inhibitor Resistance in Lung Cancer

Abstract: Despite the recent approval of third-generation therapies, overcoming resistance to epidermal growth factor receptor (EGFR) inhibitors remains a major challenge in non-small cell lung cancer. Conceptually, synthetic lethality holds the promise of identifying non-intuitive targets for tackling both acquired and intrinsic resistance in this setting. However, translating these laboratory findings into effective clinical strategies continues to be elusive. Here, we provide an overview of the synthetic lethal appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 127 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…However efficacy is often short-lived with the majority of patients going on to develop acquired resistance and tumour recurrence after prolonged drug treatment [3] . Studies in cell line models have revealed several major mechanisms of resistance that have been clinically observed, including the acquisition of drug resistant mutations in the target kinase, activation of bypass signalling pathways and phenotypic alterations such as epithelial-mesenchymal-transition (EMT) [3] , [4] , [5] , [6] . These drug resistant cells arise either from selection of pre-existing clones within a heterogeneous tumour cell population or through the adaptation and subsequent evolution of drug-tolerant persister cells [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…However efficacy is often short-lived with the majority of patients going on to develop acquired resistance and tumour recurrence after prolonged drug treatment [3] . Studies in cell line models have revealed several major mechanisms of resistance that have been clinically observed, including the acquisition of drug resistant mutations in the target kinase, activation of bypass signalling pathways and phenotypic alterations such as epithelial-mesenchymal-transition (EMT) [3] , [4] , [5] , [6] . These drug resistant cells arise either from selection of pre-existing clones within a heterogeneous tumour cell population or through the adaptation and subsequent evolution of drug-tolerant persister cells [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“… ( A ) Gatekeeper mutations on BCR–ABL restore kinase activity in the presence of BCR–ABL inhibitors (BCR–ABLi) in chronic myeloid leukaemia (ATP-binding site mutations and T315I enable resistance to first- and second-generation BCR–ABLi respectively) [ 86 ]. ( B ) Amplification of the EML4–ALK fusion restores signalling in the presence of ALK inhibitor (ALKi) crizotinib in NSCLC by increasing levels of active unbound oncogene [ 87 ].…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…DNMT1 maintains methylation patterns following DNA replication. Combining DNMT1 inhibition and PARP inhibitors cause synthetic lethality (64). PARP inhibition prevents XRCC1 interaction with several DNA repair proteins, including DNMT1 and thereby insufficient organization of base excision repair (64).…”
Section: Synthetic Lethal Gene Partners Based On Chemo Resi Stancerelmentioning
confidence: 99%
“…Combining DNMT1 inhibition and PARP inhibitors cause synthetic lethality (64). PARP inhibition prevents XRCC1 interaction with several DNA repair proteins, including DNMT1 and thereby insufficient organization of base excision repair (64). We can provide chemoresistance or stem cell-related genes for synthetic lethality pairs of PARP inhibitors in CCC.…”
Section: Synthetic Lethal Gene Partners Based On Chemo Resi Stancerelmentioning
confidence: 99%